Explore the correlations of occupational commitment, psychological resilience, job satisfaction, and burnout in kindergarten teachers’ turnover intentions in rural China - Zheng, Yanan; Wang, Xiaoyu; Yang, Li (Frontiers in Psychology, 2025)
Ensuring the stability of teachers is a crucial task in developing early care education; thus, reducing the turnover rate of kindergarten teachers is the core priority. This research explores the correlation of four antecedents with teachers’ turnover intentions: occupational commitment, psychological resilience, job satisfaction, and burnout. This study utilized a stratified sampling methodology based on regional GDP levels and implemented a hybrid data collection approach combining online and offline questionnaire distribution to ensure comprehensive representation across socioeconomic contexts. Taking the collected data from 920 kindergarten teachers in the rural area of Hebei Province, China as the research object, the research presents the following findings: (i) nearly 60% of kindergarten teachers prefer to Move rather than Leave when having turnover intentions; (ii) the improvement of psychological resilience and working conditions could effectively mitigate the decision of kindergarten teachers to leave entirely; (iii) teachers with no turnover intentions are more concerned about intrinsic motivation, but there is a risk of “false retention”; (iv) job satisfaction has the most substantial impact on kindergarten teachers’ turnover intentions, but the performance is relatively poor; (v) risk and protective factors synergistically affect teachers’ turnover intentions.